2012
DOI: 10.1242/jeb.076539
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from desiccation contributes to a genotype-by-temperature interaction for cold survival inDrosophila melanogaster

Abstract: SUMMARYSurvival at cold temperatures is a complex trait, primarily because of the fact that the physiological cause of injury may differ across degrees of cold exposure experienced within the lifetime of an ectothermic individual. In order to better understand how chill-sensitive insects experience and adapt to low temperatures, we investigated the physiological basis for cold survival across a range of temperature exposures from −4 to 6°C in five genetic lines of the fruit fly Drosophila melanogaster. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…S2). In D. melanogaster , the humidity during both heat (Bubliy et al, 2012) and cold exposure (Kobey & Montooth, 2013) alters survival rate. Combining two stressors like high temperature with low RH provides more stressful conditions to vinegar flies than high temperature with high RH (Bubliy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). In D. melanogaster , the humidity during both heat (Bubliy et al, 2012) and cold exposure (Kobey & Montooth, 2013) alters survival rate. Combining two stressors like high temperature with low RH provides more stressful conditions to vinegar flies than high temperature with high RH (Bubliy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since invasion process may trigger adaptation to novel climatic areas, data are highly needed on invasive populations submitted to a range of thermal stress intensities and durations. In Drosophila melanogaster , the humidity during thermal stress modifies survival probability and the response can be temperature-dependent (Bubliy et al, 2012; Kobey & Montooth, 2013). Combining high temperature with low humidity provides more stressful conditions to Drosophila flies than high temperature with high humidity (Bubliy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has previously been shown that dehydration exacerbates the development of chill injury in D. melanogaster, particularly at moderate cold exposure temperatures (Kobey and Montooth, 2013). It should be mentioned, however, that the water vapor deficit is very low during the cold exposure and the flies are therefore unlikely to be severely stressed by dehydration during short-term exposures (Kobey and Montooth, 2013). Secondly, it is possible that dissipation of osmotic gradients occurs within the animal as a consequence of reduced active transport at low temperatures.…”
Section: Discussion Hemolymph Osmolality Before and After Cold Exposurementioning
confidence: 99%
“…Indeed, tropical (and cold-sensitive) Drosophila species are generally also more susceptible to dehydration than xeric or coldadapted species (Kellermann et al, 2013). Further, it has previously been shown that dehydration exacerbates the development of chill injury in D. melanogaster, particularly at moderate cold exposure temperatures (Kobey and Montooth, 2013). It should be mentioned, however, that the water vapor deficit is very low during the cold exposure and the flies are therefore unlikely to be severely stressed by dehydration during short-term exposures (Kobey and Montooth, 2013).…”
Section: Discussion Hemolymph Osmolality Before and After Cold Exposurementioning
confidence: 99%